“En la república de los miopes”. Veintisiete notas a la Soledad primera de Góngora (I) - Aranda Arribas, Victoria; Bonilla Cerezo, Rafael (El Colegio de México, 2022)
This article tries to shed light on twenty-seven loci critici of Góngora’s first Solitude (1613): vv. 117-120, 153-162, 167-168, 171-175, 182-189, 212-221, 263-266, 291-296, 321-328, 344-349, 374-375, 461-464, 500-502, 573-579, 580-584, 585-589, 598-601, 623-629, 667-668, 701-704, 705-708, 810-811, 812-817, 866-871, 872-878, 895-896, 943 and 1012-1013. Taking the great edition of the Solitudes (1994) prepared by Robert Jammes as our starting point, we revise several textual readings which he considered doubtful. In  doing so, we take into account commentaries made by critics from the Baroque period (Almansa y Mendoza, Jáuregui, Abad de Rute, Díaz de Rivas, the Anonymous from Antequera, Pellicer, Salcedo Coronel, Vázquez Siruela) and also by the modern critics (Reyes, Spitzer, Alonso, Orozco, Pabst, Alatorre, Carreira, Sinicropi, Molho, Ly, Poggi, Cancelliere, Romanos, Sánchez Robayna, Lara Garrido, Yoshida, Blanco, Mazzocchi, Micó, Roses, Pérez Lasheras, Ponce Cárdenas, Collins, Tenorio, Matas Caballero, Chemris, Osuna Cabezas, Palomares, Castaldo, Román Gutiérrez, Tanabe, Rojas Castro, Conde, Encarnación…). Attention is also paid to the classical tradition, to emblems and to the dialogue between the first Solitude and the rest of Góngora’s poetic corpus.